Cryoprotective Efficiency of Media Based on Oxyethyl Derivatives of Polyols During Freezing of Human Erythrocytes - Kompaniets, A. M.; Nikolenko, O. V.; Chekanova, V. V.; Yesipova, Yu. S. (Problems of Cryobiology and Cryomedicine, 2008)
The survival of human erythrocytes during freezing depending on cryoprotective medium composition has been investigated. It has been established that cryoprotective media based on glycerol and methyl cellosolve oxyethyl derivatives, containing sucrose and mannite, increase the survival of erythrocytes after cryopreservation.